PLK4 deubiquitination by Spata2‐CYLD suppresses NEK7‐mediated NLRP3 inflammasome activation at the centrosome. (25th November 2019) - Yang, Xiao‐Dong; Li, Wenguo; Zhang, Shuangyan; Wu, Dandan; Jiang, Xiaoli; Tan, Rong; Niu, Xiaoyin; Wang, Qijun; Wu, Xuefeng; Liu, Zhiduo; Chen, Lin‐Feng; Qin, Jun; et al.
Abstract: The innate immune sensor NLRP3 assembles an inflammasome complex with NEK7 and ASC to activate caspase‐1 and drive the maturation of proinflammatory cytokines IL‐1β and IL‐18. NLRP3 inflammasome activity must be tightly controlled, as its over‐activation is involved in the pathogenesis of inflammatory diseases. Here, we show that NLRP3 inflammasome activation is suppressed by a centrosomal protein Spata2. Spata2 deficiency enhances NLRP3 inflammasome activity both in the macrophages and in an animal model of peritonitis. Mechanistically, Spata2 recruits the deubiquitinase CYLD to the centrosome for deubiquitination of polo‐like kinase 4 (PLK4), the master regulator of centrosome duplication. Deubiquitination of PLK4 facilitates its binding to and phosphorylation of NEK7 at Ser204. NEK7 phosphorylation in turn attenuates NEK7 and NLRP3 interaction, which is required for NLRP3 inflammasome activation. Pharmacological or shRNA‐mediated inhibition of PLK4, or mutation of the NEK7 Ser204 phosphorylation site, augments NEK7 interaction with NLRP3 and causes increased NLRP3 inflammasome activation. Our study unravels a novel centrosomal regulatory pathway of inflammasome activation and may provide new therapeutic targets for the treatment of NLRP3‐associated inflammatory diseases. Synopsis: NLRP3 inflammasome activation requires the interaction of NLRP3 with centrosomal kinase NEK7. Here we show that the centrosome‐localized deubiquitinase complex Spata2‐CYLD deubiquitinates centrosomal kinase PLK4 to augment its binding to and phosphorylation of NEK7, leading to reduced NEK7‐NLRP3 interaction and NLRP3 inflammasome activation. Spata2 is localized to the centrosome and suppresses NLRP3 inflammasome activation. Spata2 recruits CYLD to the centrosome to deubiquitinate PLK4. Deubiquitination of PLK4 facilitates its binding to and phosphorylation of NEK7. NEK7 phosphorylation by PLK4 attenuates NEK7‐NLRP3 interaction and NLRP3 inflammasome activation. Abstract : The centrosomal protein Spata2 is as a novel regulator of NEK7 phosphorylation and NLRP3‐mediated inflammatory responses.